Optimization of Freeze-Drying Protectants by Response Surface Methodology and Encapsulation for Bifidobacterium Pseudocatenulatum G4 and Lactobacillus Acidophilus LA-5 Survival Enhancement - Teoh, Peck Lian (2011)
Probiotic can easily lose their cell viability during processing, storage, as well as during gastrointestinal transit. Therefore, the main objective of this study was to optimize a suitable protective media combination (skim milk, sucrose, trehalose and inulin) for freeze-drying of Bifidobacterium pseudocatenulatum G4 using Response Surface Methodology (RSM) and to encapsulate both B. pseudocatenulatum G4 and Lactobacillus acidophilus LA-5 for enhanced survival during heat exposure, high sodium concentration and gastrointestinal transit. The identity of B. pseudocatenulatum G4 was confirmed by genus-specific PCR using the specific gene-targeted primers (Lm26 and Lm3). The morphology of the probiotic was also examined by microscopic method, in particular, by using the Gram-staining method and scanning electron microscope. Analysis of variance (ANOVA) showed that skim milk, sucrose and inulin concentration had significant (P < 0.05) effect on the viability of B. pseudocatenulatum G4 after freeze-drying. On the other hand, concentration of trehalose did not have any significant effect (P > 0.05) on viability of the freeze-dried cells. Optimization model indicated that a combination of 15.04% (w/v) skim milk, 2.17% (w/v) sucrose, 1.87% (w/v) trehalose and 0.36% (w/v) inulin resulted in high survival (9.86 log cfu/mL) of B. pseudocatenulatum G4. Experimental verification showed that the experimental values were adequately close to the predicted values, with no significant difference (P > 0.05) in terms of survival level of B. pseudocatenulatum G4 after freeze-drying, thus verifying the accuracy and validity of final reduced model. The next part of the research focused on encapsulation of B. pseudocatenulatum G4 and L. acidophilus LA-5 using the extrusion technique. The encapsulated probiotic were further coated with chitosan to enhance protection. The encapsulated probiotic were compared with free cells in terms of thermotolerance, sodium tolerance, simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) resistant properties. Encapsulated probiotic survived significantly (P < 0.05) better than free cells during heat exposure (55, 60 and 65 °C) up to 30 min. Encapsulated probiotic also showed higher viability when they were exposed to high sodium concentrations (1% w/v, 2% w/v and 3% w/v) for 3 h. The survival of free cells decreased with increasing sodium concentration and prolonging incubation period. However, the encapsulated cells did not show this similar trend of cell reduction. Similarly, encapsulation of probiotic resulted in significantly (P < 0.05) higher survival of cells during exposure to SGF and SIF. Free cells were not detectable after 1 h exposure to SGF, whereas the encapsulated probiotic decreased from about 9 to 5 log cfu/mL. Only approximately 3.21-4.24 log cfu/mL of encapsulated cells remained after sequential incubation in SIF. Chitosan coated alginate-starch capsules provided the best protection for both L. acidophilus LA-5 and B. pseudocatenulatum G4 during SGF and SIF exposure. Encapsulation using extrusion technique produced homogenous spherical shaped capsules. The extrusion technique tends to produce capsules with large particle size (~3.6 mm). Scanning electron micrographs showed that probiotic cells were not visible at the surface of freshly prepared capsules which had not been subjected to any treatment. All the capsules were found to retain their shape with a little shrinkage of the capsules during SGF exposure. There was drastic decrease in mechanical strength of the probiotic capsules when they were subjected to SIF, which favoured the release of probiotic cells. This ensured proper colonization of probiotic cells in the colon.